Pediatric resident use, perceptions, and desires for improvement of a clinical secure messaging application - Andrew W Halterman; Anneli R Cochrane; Andrew D Miller; Joy L Lee; William E Bennett, Jr; Emily L Mueller (Computer Methods and Programs in Biomedicine Update)
Background: Hospitals are transitioning away from traditional pagers to secure text messaging (STM) applications. STM is perceived to improve efficiency and accessibility. There is limited research on user's impressions of how STM impacts patient safety, provider wellness, and quality of patient care. Objectives: To understand the use and perceptions of a clinical STM by pediatric residents at a free-standing quaternary care children's hospital. Methods: A survey was conducted of pediatric residents regarding their experience with Diagnotes®. Demographic data were obtained along with use patterns, ability to perform tasks, and perceptions of intended purpose. Further questions evaluated agreement with communication strategies and satisfaction with features. Three open-ended questions asked about experience where STM impacted (1) patient care coordination and (2) patient safety. A final question asked for any additional STM feedback. Results: Of 169 surveys, there were 112 respondents (66.3 % response rate). Respondents unanimously endorsed daily STM use on their personal mobile devices with good knowledge of basic features. Respondents were overall satisfied with Diagnotes® (73.9 %) including the ability to communicate efficiently (84.8 %) and effectively (79.5 %). Yet only 32.1 % were satisfied with Diagnotes® training. Only 59.5 % believed Diagnotes® was appropriate for urgent patient care needs and only 43.2 % believed its purpose was to inform the team of patient emergencies. Key qualitative themes included improved coordination of patient care tasks through STM, but there were concerns raised around sending and receiving messages, the additional cognitive burden placed by STM, and differences in culture of use that created conflict. Conclusions: Diagnotes® is viewed positively including use for effective coordination of patient care and familiarity of functions of Diagnotes®. Barriers included unclear interprofessional expectations for use. Future research should incorporate a broad range of healthcare professionals' perceptions and co-creation of STM best practice guidelines for use, including around urgent or emergent patient care issues.